2022
DOI: 10.3390/joitmc8010053
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Industry 4.0 in Australia: Insights from Advanced Australian Manufacturers

Abstract: This study explores Industry 4.0 in the Australian context, where manufacturing is dominated by smaller firms servicing the domestic market. We interviewed 20 advanced Australian manufacturers from diverse fields, capturing detailed descriptions of the Industry 4.0 implementation process. We compared the themes that emerged from their descriptions with the factors typically assessed in Industry 4.0 frameworks to draw out differences in emphasis. Consistent with these frameworks, Australian manufacturers were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Managers recognised the need for recent university graduates in industrial design and engineering to learn from and work with experienced trade workers, to build the capability to design practical solutions. Consistent with other research into Australian advanced manufacturing (Mason et al, 2022), managers identified this mix of craft skills with engineering qualifications and digital skills as essential to move towards higher levels of advanced manufacturing.…”
Section: Case Studiessupporting
confidence: 70%
See 3 more Smart Citations
“…Managers recognised the need for recent university graduates in industrial design and engineering to learn from and work with experienced trade workers, to build the capability to design practical solutions. Consistent with other research into Australian advanced manufacturing (Mason et al, 2022), managers identified this mix of craft skills with engineering qualifications and digital skills as essential to move towards higher levels of advanced manufacturing.…”
Section: Case Studiessupporting
confidence: 70%
“…Prior research also supports the need to develop strategic business skills before building digital capabilities (Jayawarna et al, 2006). Management development in SMEs is traditionally under-resourced, so it is important to emphasise that investment in management development can drive product and technology innovation (Mason et al, 2022). The findings from this study suggest that for innovation, management development must include formal education/ qualifications and ongoing participation in a broad range of professional development activities.…”
Section: Management Development To Understand and Lead Innovationmentioning
confidence: 72%
See 2 more Smart Citations
“…The lack of published studies on AR/VR uptake in Australian manufacturing supply chains likely reflects slower rates of technology adoption and shrinkage in the manufacturing sector in the last decade (Andrews et al, 2022) and industry policy that has focused on high export industries like agriculture and mining (Australian Government, 2019; Standford, 2016). These factors have produced a higher representation of small–medium enterprises, with fewer resources for technology investment and R&D (Mason et al, 2022). In addition, recent survey data of Australian supply chain practitioners ( n = 188) indicates AR/VR is perceived to have a low impact on the supply chain, with greater focus being placed on the adoption of robotics in manufacturing (Hopkins, 2021).…”
Section: Introductionmentioning
confidence: 99%